Mechanism of As(V) adsorption from aqueous solution by chitosan-modified diatomite adsorbent. Issue 10 (1st August 2022) - Ma, Lili; Xu, Hui; Xie, Qinglin; Chen, Nanchun; Yu, Qingfeng; Li, Cong
Abstract: Arsenic poses severe threats to human and ecosystem health. Various methods for arsenic removal, including the use of different adsorbents, have been employed. Herein, an adsorbent using refined diatomite as the matrix and chitosan as the modifying agent was evaluated. For effective design of adsorption systems, the structural changes during adsorbent modification and the adsorption process were investigated. The adsorbent was analyzed and characterized using scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), x-ray diffraction (XRD), and x-ray photoelectron spectroscopy (XPS). The feasibility of using chitosan-modified diatomite was explored by utilizing the batch equilibrium technique with varying experimental parameters, including the adsorbent dose, initial concentration of As(V), temperature, pH, and time. Additionally, chitosan-modified diatomite adsorption isotherms and adsorption kinetics were studied. The ability of the adsorbent to remove As(V) from an aqueous solution before and after modification was investigated via a static adsorption experiment. No change was found in the diatomite matrix after modification; however, the adsorption peaks of the functional groups changed. The organic phase peak revealed by XRD disappeared, whereas a nitrogen phase peak appeared. During modification, open chains of chitosan were grafted effectively onto the diatomite surface. Chitosan-modified diatomite can be used to coordinate an adsorption reaction with arsenate through surface –NH2 . The optimum conditions for adsorption at an initial As(V) concentration of 2 mg/L were a pH of 5, temperature of 25 °C, reaction time of 60 min, and an adsorbent dose of 3 g/L. Chitosan-modified diatomite can remove As(V) from aqueous solutions significantly better than unmodified diatomite. Graphical Abstract: UF0001